Dynamics between denial and moral panic: The identification of convicted sex offenders in the community. (March 2016) - Boone, Miranda; van de Bunt, Henk
In this contribution the authors describe the main findings of a research study conducted in the Netherlands on the return of sex-offenders to the community. The study questioned how crisis situations can develop following the identification of a sex-offender in the community. The study consisted of an analysis of ten cases in which the return of a convicted sex offender to the community or the 'discovery' of a sex-offender in the community resulted in community unrest and attracted media attention. Interviews were conducted with professionals involved in supervising those individuals convicted for sexual offences as well as the individuals themselves. Contrary to the situation in both the United States and the United Kingdom, criminal records in the Netherlands − as in most of continental Europe − are predominantly seen as a private matter and are not made public to those outside the criminal justice system. The article also examines the role of the local Mayor who has a central role in managing the local negative reactions to return of those convicted of sexual offences back into the community in the Netherlands. The findings produced from the data are analysed applying a social construction approach that utilizes the concepts of 'moral panic' and denial. The authors found that the return of a those convicted of sexual offences can lead to a range of responses varying from anger and panic to secrecy and denial. Ultimately the authors found that greater transparency led to more positive outcomes in these cases.